2002
DOI: 10.4049/jimmunol.169.10.5926
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Complement Anaphylatoxin C3a Receptor Suppresses Th2 Effector Functions in a Murine Model of Pulmonary Allergy

Abstract: Asthma is a chronic inflammatory disease of the lung resulting in airway obstruction. The airway inflammation of asthma is strongly linked to Th2 lymphocytes and their cytokines, particularly IL-4, IL-5, and IL-13, which regulate airway hyperresponsiveness, eosinophil activation, mucus production, and IgE secretion. Historically, complement was not thought to contribute to the pathogenesis of asthma. However, our previous reports have demonstrated that complement contributes to bronchial hyperreactivity, recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 55 publications
9
149
3
Order By: Relevance
“…These results show that suppression of the late-phase increase in airway resistance and AHR by the antagonist or the mAb was not related to the production of Th2-type cytokines. However, there have been conflicting reports: C3a receptor-deficient mice sensitized with mixed OVA and Aspergillus fumigatus (44) or house dust mites (45) showed reduced cytokine levels and AHR. Kumar and Foster (46) have suggested that the roles of cells and molecules in AHR were altered by changing the protocol (dose and duration) for the challenge, indicating that the role of C3a in the pathogenesis of asthma also varies depending on the protocol used.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that suppression of the late-phase increase in airway resistance and AHR by the antagonist or the mAb was not related to the production of Th2-type cytokines. However, there have been conflicting reports: C3a receptor-deficient mice sensitized with mixed OVA and Aspergillus fumigatus (44) or house dust mites (45) showed reduced cytokine levels and AHR. Kumar and Foster (46) have suggested that the roles of cells and molecules in AHR were altered by changing the protocol (dose and duration) for the challenge, indicating that the role of C3a in the pathogenesis of asthma also varies depending on the protocol used.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been shown for C3a. Specifically, several groups have now shown that deficiencies in C3 (21,22) or the C3aR (7,23,24) protect against the development of allergen-driven AHR. Likewise, the AHR induced by exposure to several environmental stimuli, including RSV (11), particulate matter (22), and ozone (9), has been shown to be C3-dependent.…”
Section: Complement Pathway Regulation Of Allergic Effector Pathwaysmentioning
confidence: 99%
“…Local production of C3 by dendritic cells in mice, for example, promotes Th1 development (41,47). C3a can amplify pathologic process by increasing vasopermeability, contracting bronchial smooth muscle, stimulating dendritic cells to modulate T cell activation, or activating mast cells and basophils, of likely importance in allergic disorders such as asthma and in autoimmune urticaria (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98). Furthermore, C3adesArg, a metabolite of C3a, serves as an adipokine associated with obesity, type II diabetes, and coronary artery disease (99).…”
Section: Discussionmentioning
confidence: 99%